Synthesis, spectroscopic characterization and dyeing performance of novel bis azo dyes derived from benzidine - Alaa Z. Omar; Mohamed A. El-Rahman; Ezzat A. Hamed; Samir K. El-Sadany; Mohamed A. El-atawy (Scientific Reports, 2023)
Abstract Benzidine was coupled with ethyl cyanoacetate, and malononitrile, to give azo-hydrazo products which in turn were cyclized by using hydrazine and phenyl hydrazine to give 4,4'-([1,1'-biphenyl]-4,4'-diylbis(hydrazin-2-yl-1-ylidene))bis pyrazole derivatives 5–7. These compounds were identified by various spectral analysis. The examination of 0.1 M NaOH and 0.1 M HCl in DMF revealed that the λmax of the synthesized dyes are quite sensitive to pH variation and slightly affected by the coupler moieties. Utilizing the dispersion agent DYEWELL-002, polyester fabric (PE-F) was dyed in water. The color strength (K/S), its summation (K/Ssum), dye exhaustion (%E) and reflectance values were measured and discussed. The DFT method estimates the chemical descriptor parameters of the titled dyes, using B3LYP/6-31G(d,p) level to investigate the performance of dyes as well as to postulate a mechanism of dyeing process.